Pengaruh Sosialisasi Pajak, Pengetahuan Pajak, dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Sadina Hapsarini Putri; Nyimas Wardatul Afiqoh (Journal of Culture Accounting and Auditing, 2023)
This study aims to determine tax socialization, tax knowledge and tax sanctions on individual taxpayer compliance. The population in this study are all individual taxpayers registered who are registered KPP Pratama Gresik. Sampling uses random sampling method and the total sampleis 105 respondents. Show that tax socialization has no effect on individual taxpayer. Meanwhile, tax knowledge and tax sanctions have an effect on individual taxpayer compliance.This study has limitations using only a relatively small number of samples due to limited time for distributing questionnaires and researchers can add the number of respondents to increase the number of samples so that further research is better.